High-corrosion-resistance low-temperature welding strip and preparation method thereof

By coating a specific coating liquid on the surface of the photovoltaic welding tape to form a solid film layer, the corrosion resistance and reliability problems of the low-temperature welding tape in photovoltaic cell welding are solved, and the high corrosion resistance and strength of the welding tape are improved.

CN119604042APending Publication Date: 2025-03-11WUXI SVECK TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411566577.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing low-temperature welding tapes have corrosion resistance and reliability problems in photovoltaic cell welding, especially the electrochemical corrosion speed of bismuth-containing welding tapes, resulting in reduced reliability.

Method used

By coating a coating liquid including rosin, bisphenol A type epoxy resin, active agent, curing agent, imidazole promoter, surfactant and other additives on the surface of the solder tape, a solid coating film layer is formed to protect the tin tape from corrosion for a long time and improve the welding strength.

Benefits of technology

This method significantly improves the corrosion resistance and reliability of the welding tape, can easily pass the DH2000 test, and there is almost no solder joint peeling after the TC200 test. The higher the bismuth content, the more obvious this advantage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention is suitable for the technical field of solder strip preparation, and provides a high-corrosion-resistance low-temperature solder strip and a preparation method thereof.The preparation method comprises the following steps that a photovoltaic solder strip is sequentially subjected to the procedures of forming, annealing and hot tinning, a tin strip is obtained, the tin strip is cooled after being taken out of a tin furnace, when the temperature is reduced to 130-150 DEG C, the surface of the tin strip is evenly coated with coating liquid through a specific tool, and the high-corrosion-resistance low-temperature solder strip is obtained. And rapidly volatilizing the solvent by using the heat of the tin strip and external auxiliary heat to obtain the photovoltaic welding strip with a solid coating film layer. The coating liquid comprises the following raw materials in percentage by mass: 10-20% of rosin, 15-25% of bisphenol A epoxy resin, 0.2-5% of an active agent, 5-10% of a curing agent, 0.05-0.1% of an imidazole accelerant, 0.2-1% of a surfactant, 0.5-2% of other additives and the balance of a solvent. By generating a layer of cured resin film on the surface of the solder strip, the solder strip can be protected from corrosion for a long time, and the welding strength is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding strip preparation, and in particular relates to a high-corrosion-resistant low-temperature welding strip and a preparation method thereof. Background Art

[0002] Traditional photovoltaic cell welding usually uses Sn60Pb eutectic solder, which has the best comprehensive performance. In addition, the standard electrode potentials of tin and lead are very close, so the alloy has outstanding resistance to electrochemical corrosion. Therefore, the reliability of tin-lead solder strips has been relatively stable. With the development of HJT cells and the advancement of ultra-thin cells, the demand for low-temperature welding in the welding process of photovoltaic cells has increased. Low-temperature solder strips usually use bismuth-containing solder. As the bismuth content increases, the melting point of the solder will gradually decrease within a certain range. For example, Sn42Bi58 solder has a liquidus temperature of 138°C; Sn43Pb43Bi14 solder has a liquidus temperature of 168°C. Although bismuth-containing solder can reduce the welding temperature, bismuth is brittle, has poor corrosion resistance, and has a large potential difference with tin, resulting in fast electrochemical corrosion of bismuth-containing solder and reduced reliability. In particular, in specific applications, it was found that the reliability of bismuth-containing solder strips is significantly lower than that of tin-lead solder strips. After the DH2000 test, it is easy to turn yellow and black, and the higher the bismuth content, the more obvious the phenomenon. Especially for lead-free tin-bismuth solder strips, DH1000 can cause serious yellowing of the solder strips. In addition, the strength of tin-bismuth solder is relatively low, which will also cause solder joint failure after the TC200 test, resulting in higher power attenuation than tin-lead solder strips. These situations are the difficulties faced by low-temperature solder strips, and are also the biggest technical obstacles to the low-temperature welding of photovoltaic cells.

[0003] How to improve the corrosion resistance and reliability of bismuth-containing low-temperature solder strips is an important topic for low-temperature and lead-free solder strips. The development and selection of solder for photovoltaic solder strips mostly refer to SMT solder technology. In terms of improving corrosion resistance and reliability, SMT solders mostly use the addition of trace auxiliary elements for local improvement. However, this improvement effect is limited and does not meet the use requirements of solder. Improving the reliability of the solder itself is not feasible at this stage. For this reason, the present invention proposes a high-corrosion-resistant low-temperature solder strip and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a high corrosion resistance low temperature welding strip and a preparation method thereof, aiming to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a high corrosion-resistant low-temperature welding strip comprises the following steps:

[0007] The photovoltaic welding ribbon is successively subjected to forming, annealing, and hot-dip tinning processes to obtain a tin ribbon. After the tin ribbon is taken out of the tin furnace, it is cooled. When the temperature drops to 130-150°C, the coating liquid is evenly applied to the surface of the tin ribbon through a specific tooling, and the solvent is quickly volatilized by the heat of the tin ribbon itself and external auxiliary heat to obtain a photovoltaic welding ribbon with a solid coating film layer.

[0008] The coating liquid comprises the following raw materials in mass content: 10-20% rosin, 15-25% bisphenol A epoxy resin, 0.2-5% activator, 5-10% curing agent, 0.05-0.1% imidazole accelerator, 0.2-1% surfactant, 0.5-2% other additives, and the balance is solvent.

[0009] Furthermore, the preparation method of the coating liquid is as follows:

[0010] Step 1, pour the weighed bisphenol A epoxy resin into the solvent, heat to 60°C in a sealed state, ultrasonically stir for 40 to 60 minutes to completely dissolve the resin, and then cool and stand;

[0011] Step 2: Pour the rosin into a container and stir at room temperature for 30 to 60 minutes to form a uniform solution;

[0012] Step 3: Add the weighed active agent, surfactant, imidazole accelerator and other additives into the container in turn, stir at room temperature for 30 to 60 minutes, cool to room temperature after all substances are dissolved, add curing agent, heat to 70°C, stir for 30 minutes, obtain the coating liquid, and seal for storage.

[0013] Furthermore, the softening temperature of the rosin is 60-100°C.

[0014] Furthermore, the N value of the bisphenol A epoxy resin is 4-7.

[0015] Furthermore, the activator includes one or more of oxalic acid, malonic acid, glutaric acid, DL-malic acid, succinic acid, adipic acid, and phthalic acid organic acids, and one or more of monoethanolamine, triethanolamine, and stearic acid amide amine active agents.

[0016] Furthermore, the curing agent is a polyacid or anhydride.

[0017] Furthermore, the solvent is an alcohol-based solvent.

[0018] A high corrosion-resistant low-temperature welding strip is prepared according to the preparation method described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention improves the corrosion resistance of the solder strip by means of surface protection; the present invention forms a layer of cured resin film on the surface of the solder strip, and the cured resin film can protect the tin strip from corrosion for a long time, and can easily pass the DH2000 test. At the same time, because the cured resin film itself plays the role of bonding the solder strip and the battery cell, the welding strength is greatly improved, and there is almost no phenomenon of solder joint falling off after the TC200 test. The higher the bismuth content, the more obvious this advantage is. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0023] The present invention coats a film layer with a fluxing effect on the surface of the photovoltaic welding ribbon, so that welding with the battery cell can be achieved without using traditional flux, and the film layer also has surface protection. The principle of the present invention is as follows:

[0024] A thermosetting resin is added to the pre-coated flux. Before adding a curing agent, the resin is in a thermoplastic state within a certain temperature range. When the soldering ribbon and the battery cell are welded, the curing effect has not yet begun, so the resin softens together with the soldering film, and the active substances in the film layer begin to play a role, realizing the welding of the soldering ribbon and the battery cell. Since the welding time is very short, the resin does not have time to undergo a curing reaction, so the resin will be wrapped on the surface of the soldering ribbon after welding. When the battery pack is laminated, the resin undergoes a curing reaction at a high temperature to form a thermosetting state, and eventually a cured resin film layer will be formed on the surface of the soldering ribbon and the surface where the soldering ribbon and the grid line meet. The cured resin film layer has two important functions: 1) It isolates the acetate ions and hydrogen ions generated by the EVA film from contacting the soldering tape, thereby preventing the soldering tape from electrochemical oxidation and improving the corrosion resistance of the soldering tape; 2) The cured resin film itself has a bonding function, which can improve the bonding strength between the soldering tape and the battery cell, and the thermal expansion coefficient of the cured resin film is higher than that of the battery cell, so it will not crack or peel off due to the thermal expansion of the substrate, and can fix the battery cell and the soldering tape for a long time, thereby improving welding reliability.

[0025] One embodiment of the present invention provides a method for preparing a high corrosion-resistant low-temperature solder strip, comprising the following steps:

[0026] The photovoltaic welding ribbon is sequentially subjected to the processes of forming, annealing and hot-dip tinning to obtain a tin ribbon. The tin ribbon is cooled after coming out of the tin furnace. When the temperature drops to 130-150°C, the coating liquid is evenly applied to the surface of the tin ribbon through specific tooling, and the solvent is quickly evaporated by the tin ribbon's own heat and external auxiliary heat to obtain a photovoltaic welding ribbon with a solid coating film layer. This type of welding ribbon has high corrosion resistance after lamination and curing.

[0027] The coating liquid comprises the following raw materials in mass content: 10-20% rosin, 15-25% bisphenol A epoxy resin, 0.2-5% activator, 5-10% curing agent, 0.05-0.1% imidazole accelerator, 0.2-1% surfactant, 0.5-2% other additives, and the balance is solvent.

[0028] In the embodiment of the present invention, for the selection of thermosetting resin, the resin is required to be solid at room temperature and have the characteristics of linear thermoplasticity before curing; since curing is required to be completed during lamination, a curing temperature of 120 to 140°C is required, and curing will not occur before this temperature is reached. All curing agents should not conflict with the soldering system, and it is best to be universal; the cured resin has good acid resistance. In summary, we choose bisphenol A epoxy resin. Since high-temperature curing is adopted, polyacids or acid anhydrides are selected as high-temperature curing agents, and the curing agent content is 5 to 10%. Hydrogenated rosin with a softening temperature of 60 to 100°C is preferred, which has both film-forming agent and soldering function. The N value of bisphenol A epoxy resin is preferably 4 to 7. This type of epoxy resin has a softening point of 80 to 140°C and is the main component of the curing resin. Before the resin is fully cured, it will not affect the wettability of the solder. The activator includes organic acids such as oxalic acid, malonic acid, glutaric acid, DL malic acid, succinic acid, adipic acid, phthalic acid, etc., and one or more of amine activators such as monoethanolamine, triethanolamine, and stearic acid amide are compounded, and organic anhydrides are added as latent curing agents. Since polyacids can also produce curing effects at high temperatures, the content of anhydrides can be appropriately reduced, and the total amount of activators is 0.2-5%, preferably 0.8-3%. When the bismuth content is below 20%, the solder wettability is strong, and neutral or weak acid surfactants such as acetylene glycol and span\op surfactants can be used; when the bismuth content is greater than 20%, as the bismuth content increases, the wettability will decrease, so it is appropriate to consider using a strong acid surfactant, such as cyclohexylamine hydrobromide. Other additives include antioxidants such as 2,3-dibromo-1,2-butene diol, hydroquinone, catechol, and 2-pentylbenzimidazole. The solvent is preferably an alcohol-based solvent such as ethanol and isopropanol.

[0029] As a preferred embodiment of the present invention, the preparation method of the coating liquid is as follows:

[0030] Step 1, pour the weighed bisphenol A epoxy resin into the solvent, heat to 60°C in a sealed state, and ultrasonically stir for about 40 to 60 minutes to completely dissolve the resin, then cool and let stand;

[0031] Step 2: Pour the rosin into a container and stir at room temperature for 30 to 60 minutes to form a uniform solution. A small amount of precipitation may occur at this time, which does not need to be treated.

[0032] Step 3: Add the weighed active agent, surfactant, imidazole accelerator and other additives into the container in turn, stir at room temperature for 30 to 60 minutes, cool to room temperature after all substances are dissolved, add curing agent, heat to 70°C, stir for 30 minutes, obtain the coating liquid, and seal for storage.

[0033] One embodiment of the present invention provides the use of a high corrosion resistance low temperature welding strip (hereinafter referred to as welding strip) prepared according to the above-mentioned preparation method, as follows:

[0034] This type of soldering tape is used in the same way as conventional soldering tape, but no flux is required before soldering. During soldering, since the soldering temperature is usually between 180 and 190°C and the soldering time is between 1.5 and 2 seconds, the rosin and bisphenol A epoxy resin soften into a liquid state, and the activator is activated to promote the soldering of the soldering tape and the battery cell. Due to the short heating time, the bisphenol A epoxy resin does not have time to solidify, and will adhere to the surface of the soldering tape together with the residual rosin and curing agents such as anhydride. After that, the battery assembly enters the lamination stage, and the lamination environment is heated to 130 to 140°C in a vacuum atmosphere and kept warm for 15 to 20 minutes. In this environment, the bisphenol A epoxy resin reacts with the curing agent, undergoes a thermosetting change, and forms a layer of cured resin film on the surface of the soldering tape. This film layer can isolate water vapor, acetate and other EVA decomposition products from contacting the soldering tape, thereby keeping the soldering tape free from oxidation and corrosion for a long time. At the same time, the cured resin film has strong adhesion and can stick the soldering ribbon and the battery cell tightly together. In this way, the soldering ribbon and the battery cell form a double bond, namely welding force + bonding force, thereby improving the peeling strength and making the soldering ribbon and the battery cell have a better bonding effect.

[0035] In the embodiment of the present invention, generally, the soldering strip containing more than 15% bismuth is likely to have the problem of blackening and yellowing of the soldering strip and obvious power attenuation after the DH1000 test and the TC200 test. The higher the bismuth content, the more obvious this phenomenon is. However, the use of the high corrosion-resistant and low-temperature photovoltaic soldering strip in the present invention can completely improve this phenomenon. The cured epoxy resin film can protect the tin strip from corrosion for a long time and can easily pass the DH2000 test. At the same time, because the solid coating film layer itself plays the role of bonding the soldering strip and the battery cell, the welding strength is greatly improved. After the TC200 test, there is almost no phenomenon of solder joints falling off. The higher the bismuth content, the more obvious this advantage is. Traditional Sn42Bi58 solder is difficult to pass both the aging test and the thermal cycle test, so it has not been used. However, after the coating treatment, it not only greatly improves the welding reliability, but also eliminates the risk of easy oxidation and discoloration, making the use of tin-bismuth eutectic solder feasible, and providing strong support for the low temperature process of the soldering strip.

[0036] Embodiment 1: One embodiment of the present invention provides a method for preparing a high corrosion resistant low temperature welding strip and the use of the prepared high corrosion resistant low temperature welding strip, as follows:

[0037] Photovoltaic ribbon solder is Sn 43 Pb 43 Bi 14 , the liquidus temperature is 168°C, and the welding temperature is 190-200°C;

[0038] The coating solution includes the following raw materials by mass:

[0039] Hydrogenated rosin 10%;

[0040] Bisphenol A epoxy resin 15%;

[0041] Active agent: DL malic acid 0.3%, glutaric acid 0.2%, adipic acid 0.8%, triethanolamine 0.3%;

[0042] Surfactant: OP-10 0.2%, acetylene glycol 0.3%;

[0043] Other additives: hydroquinone 0.4%; 2-pentylbenzimidazole 0.3%;

[0044] Curing agent: phthalic anhydride 5%;

[0045] Imidazole accelerator: methylimidazole 0.1%;

[0046] The balance is ethanol.

[0047] Using the above coating liquid, when the temperature of the tin strip reaches 140±10℃, it is coated on the surface of the tin strip through a special tooling, and the solvent is quickly evaporated by using the temperature of the tin strip and external auxiliary heat to obtain a photovoltaic solder strip with a solid coating film layer. The solder strip is welded to the battery cell at 190℃, and kept at 140℃ for 20 minutes to simulate the lamination conditions to achieve complete curing of the coating, and then the battery cell with the solder strip is placed in a salt spray test chamber for a neutral salt spray test. Usually, a solder layer with a bismuth content of more than 10% will have corrosion spots within 48 hours, and a solder layer with a bismuth content of more than 20% will have corrosion spots within 24 to 36 hours. This sample can withstand a 96-hour salt spray test, indicating that its corrosion resistance is greatly enhanced.

[0048] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A method for preparing a high corrosion-resistant low-temperature solder strip, characterized in that: The following steps are involved: The photovoltaic welding ribbon is successively subjected to forming, annealing, and hot-dip tinning processes to obtain a tin ribbon. After the tin ribbon is taken out of the tin furnace, it is cooled. When the temperature drops to 130-150°C, the coating liquid is evenly applied to the surface of the tin ribbon through a specific tooling, and the solvent is quickly volatilized by the heat of the tin ribbon itself and external auxiliary heat to obtain a photovoltaic welding ribbon with a solid coating film layer. The coating liquid comprises the following raw materials in mass content: 10-20% rosin, 15-25% bisphenol A epoxy resin, 0.2-5% activator, 5-10% curing agent, 0.05-0.1% imidazole accelerator, 0.2-1% surfactant, 0.5-2% other additives, and the balance is solvent.

2. The method for preparing a high corrosion resistance low temperature solder strip according to claim 1, characterized in that: The preparation method of the coating liquid is as follows: Step 1, pour the weighed bisphenol A epoxy resin into the solvent, heat to 60°C in a sealed state, ultrasonically stir for 40 to 60 minutes to completely dissolve the resin, and then cool and stand; Step 2: Pour the rosin into a container and stir at room temperature for 30 to 60 minutes to form a uniform solution; Step 3: Add the weighed active agent, surfactant, imidazole accelerator and other additives into the container in turn, stir at room temperature for 30 to 60 minutes, cool to room temperature after all substances are dissolved, add curing agent, heat to 70°C, stir for 30 minutes, obtain the coating liquid, and seal for storage.

3. The method for preparing a high corrosion-resistant low-temperature solder strip according to claim 1, characterized in that: The softening temperature of the rosin is 60-100°C.

4. The method for preparing a high corrosion resistance low temperature solder strip according to claim 1, characterized in that: The N value of the bisphenol A epoxy resin is 4-7.

5. The method for preparing a high corrosion resistance low temperature solder strip according to claim 1, characterized in that: The activator includes one or more of oxalic acid, malonic acid, glutaric acid, DL malic acid, succinic acid, adipic acid, and phthalic acid organic acids, and one or more of monoethanolamine, triethanolamine, and stearic acid amide amine activators.

6. The method for preparing a high corrosion resistance low temperature solder strip according to claim 1, characterized in that: The curing agent is a polyacid or anhydride.

7. The method for preparing a high corrosion resistance low temperature solder strip according to claim 1, characterized in that: The solvent is an alcohol-based solvent.

8. A high corrosion resistance low temperature welding strip prepared according to the preparation method described in any one of claims 1 to 7.

Citation Information

Cited By

  • A tin-bismuth composite solder, a preparation method thereof and a solder strip

    CN122807373A